Whole exome sequencing in family trios reveals de novo mutations in PURA as a cause of severe neurodevelopmental delay and learning disability. Issue 12 (23rd October 2014) - Hunt, David; Leventer, Richard J; Simons, Cas; Taft, Ryan; Swoboda, Kathryn J; Gawne-Cain, Mary; ,; Magee, Alex C; Turnpenny, Peter D; Baralle, Diana
Abstract : Background: De novo mutations are emerging as an important cause of neurocognitive impairment, and whole exome sequencing of case-parent trios is a powerful way of detecting them. Here, we report the findings in four such trios. Methods: The Deciphering Developmental Disorders study is using whole exome sequencing in family trios to investigate children with severe, sporadic, undiagnosed developmental delay. Three of our patients were ascertained from the first 1133 children to have been investigated through this large-scale study. Case 4 was a phenotypically isolated case recruited into an undiagnosed rare disorders sequencing study. Results: Protein-altering de novo mutations in PURA were identified in four subjects. They include two different frameshifts, one inframe deletion and one missense mutation. PURA encodes Pur-α, a highly conserved multifunctional protein that has an important role in normal postnatal brain development in animal models. The associated human phenotype of de novo heterozygous mutations in this gene is variable, but moderate to severe neurodevelopmental delay and learning disability are common to all. Neonatal hypotonia, early feeding difficulties and seizures, or 'seizure-like' movements, were also common. Additionally, it is suspected that anterior pituitary dysregulation may be within the spectrum of this disorder. Psychomotor developmental outcomes appear variable between patients, and we propose a possible genotype–phenotype correlation, with disruption of Pur repeat III resulting in a more severe phenotype. Conclusions: These findings provide definitive evidence for the role of PURA in causing a variable syndrome of neurodevelopmental delay, learning disability, neonatal hypotonia, feeding difficulties, abnormal movements and epilepsy in humans, and help clarify the role of PURA in the previously described 5q31.3 microdeletion phenotype.